(untitled) (Scientific journal of the Fergana State University, 2025)
This article focuses on the analysis of the interrelationships of national and cultural factors in English speech etiquette, their place in the communication process. Within the framework of the study, such qualities as understatement, small talk, dark humor, characteristic of English speech culture, are also studied, and the mechanisms of their reflection in speech are also considered.